NtGNL1 is involved in embryonic cell division patterning, root elongation, and pollen tube growth in tobacco - Wang, Lu (The New phytologist, 2008)
The function of the ARF-GEF family has drawn great attention recently, especially GNOM and GNL1, owing to their important role in plant development. A homolog of GBF was identified in Nicotiana tabacum, named NtGNL1, which is ubiquitously expressed throughout the tobacco life cycle. In NtGNL1 RNAi plants, irregular orientation of cell division and asynchronous cell development during early embryogenesis disrupted the symmetry of the developing embryo. In addition, root growth in transgenic lines was significantly slower than that in wild-type plants, although the structure of the root tip was largely intact. Pollen germination and pollen tube growth were also inhibited in the transgenic lines, and the tip of the pollen tube presented various aberrant morphologies in one of the transgenic lines. The phenotypes of different NtGNL1 RNAi transgenic lines suggest that the NtGNL1 is likely to be involved not only in embryogenesis and postembryonic development, but also in sexual reproduction; thus, NtGNL1 may play multiple and critical roles in plant development